(untitled) - Singh, Virendra P. (Bangkok, ThaiLand, 1985)
Contents: Acid sulfate soils, formation of acid sulfate soils, production of acidity, soil survey, soil analysis and evaluation of data...
Keywords: Aquatic ecology